Analysis of factors affecting the intensity of mobile transportation applications usage in Pekanbaru - Charles, Kenny; Gui, Anderes; Fernando, Yudi; Ikhsan, Ridho Bramulya; Ernawaty, .; Gabby, Maria (IEEE Publishing, 2022)
This study was made to analyzes the factors that affects the intensity of mobile transportation applications usage in Pekanbaru. This study is intended to find the correlation between behavioral intention to use main factor such as service value, service quality, and satisfaction. In this study, researcher is using quantitative research as the research method. Purposive sampling was used to collect the data. The data collection of this study is survey. While the survey's link was up from 12th June to 29th June 2022, it collected a final amount of 238 respondents. The survey is made with google forms and shared through online groups on Line, WhatsApp, and Discord that is populated with Pekanbaru residents. This study target respondent is for those who has stayed in Pekanbaru and has already used mobile transportation application in Pekanbaru. 2 hypotheses are rejected in this study as the result of this study. The hypotheses are perceived usefulness and perceived enjoyment has a positive relationship, satisfaction and behavioral intention has a positive relationship. This study found that service value and service quality are the main driver of behavioral intention to use the service. Although satisfaction doesn't serve as main driver of behavioral intention, it still affects the usage of the application. Limitation of this studies is the sample size that can be improved by further studies that add new variables such as accessibility and security.